Synergy between Village-Owned Enterprises and Merah Putih Village Cooperatives: The Road to Economic Independence - Kusumasari, Lita (Universitas Bhayangkara Surabaya, 2025)
Village-Owned Enterprises (BUMDes) and Red and White Village Cooperatives (Kopdes) are two important pillars for the people's economy. These two institutions are expected to be able to improve the welfare of village communities, contribute to economic growth, increase employment opportunities, and reduce urbanization. The purpose of the study is to provide a comprehensive picture of the collaboration between BUMDes and the Red and White Cooperative. The research method uses a qualitative descriptive approach by collecting secondary data. The results of the study state that BUMDes and Cooperatives contribute to economic growth and increase village community income. Contributions to growth can be optimized by identifying problems faced from the type of business, human resources, capital, employment opportunities, and urbanization. To overcome this, synergy is needed between the Government, Private Sector, and Universities that are members of the triple helix for each party to contribute according to their role. The success of BUMDes and the Red and White Cooperative requires a local-based business development strategy, collaboration with external parties, capacity building and training, use of technology and innovation, and diversification of products and services.